Delegation to automaticity: the driving force for cognitive evolution? - Shine, James; Shine, Richard (Frontiers in Neuroscience, 2014)
The ability to delegate control over repetitive tasks from higher to lower neural centres may be a fundamental innovation in human cognition. Plausibly, the massive neurocomputational challenges associated with the mastery of balance during the evolution of bipedality in proto-humans provided a strong selective advantage to individuals with brains capable of efficiently transferring tasks in this way. Thus, the shift from quadrupedal to bipedal locomotion may have driven the rapid evolution of distinctive features of human neuronal functioning. We review recent studies of functional neuroanatomy that bear upon this hypothesis, and identify ways to test our ideas.